Linear and whorled nevoid hypermelanosis in a 6 year old boy. - Caporelli, N.; Postacchini, V.; Simonetti, O.; Morroni, M.; Cordiali, R.; Ficcadenti, A.; Offidani, A. (European Journal of Pediatric Dermatology, 2016)
A case of linear and whorled nevoid hypermelanosis with multisystem malformations in a 6 year old boy was reported. The Authors discussed the differential diagnosis and the chromosome, pathological and ultramicroscopy alterations of the patient.